ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL SEGIEMPAT DAN SEGITIGA - Sipa Sipa; Indah Puspita Sari (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The purpose of this study is to be able to explain the various types of errors when completing the quadrilateral and triangle tests. In this study using a qualitative descriptivemethod. This study was followed by the state junior high school students of 5 Cipongkor class VIII the number of which was 24 people. The test  instrument used is in the form of 6 questions in the form of a description. The data collected in this study are tests and documentation. Based on the analysis that has been carried out the results obtained are 1) misunderstood the language quadrilaterals and triangles 2) quadrilaterals and triangle concept error 3) errors in principle. Of all kinds of errors students make more mistakes when when working on questions namely errors in understanding the language of the questions.